Isolation and identification of bacteria adversely affecting hide and leather quality - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 1996)
Two hundred and twenty five hide and chrome tanned leather samples were examined at different stages of processing to characterize the populations of organisms inhabiting them. Bacillus subtilis, Bacillus cereus, Bacillus pumilus, Bacillus licheniformis, Bacillus megaterium, Bacillus sphaericus, Micrococcus luteus, Staphylococcus aureus, Micrococcus rubens, Kurthia variabilis, Pseudomonas aeruginosa, Staphylococcus epidermidis, Bacillus brevis, Micrococcus candidus, Micrococcus roseus, Bacillus firmus and Bacillus laterosporus were isolated and identified in different stages of tannery processing. Bacillus brevis, Bacillus cereus, Bacillus firmus, Bacillus laterosporus, Bacillus licheniformis, Bacillus megaterium, Bacillus pumilus Bacillus sphaericus, Bacillus subtilis, Micrococcus luteus, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis were positive for gelatin hydrolysis. Fresh and salted hide samples were also evaluated chemically and histologically. Some of the salted hide samples showed histological changes resulting from poor curing techniques and high moisture content. It has been noted that generally Bacillus species caused deterioration of hides. It is concluded that the hide damage is caused by inadequate curing, bacterial action and autolysis.